Photo-Induced Cell Damage Analysis for Single- and Multifocus Coherent Anti-Stokes Raman Scattering Microscopy - Minamikawa, Takeo; Murakami, Yoshinori; Matsumura, Naokazu; Niioka, Hirohiko; Fukushima, Shuichiro; Araki, Tsutomu; Hashimoto, Mamoru (Journal of Spectroscopy, 2017)
In this study, we investigated photo-induced damage to living cells during single- and multifocus excitations for coherent anti-Stokes Raman scattering (CARS) imaging. A near-infrared pulsed laser (709 nm) was used to induce cell damage. We compared the photo-induced cell damage in the single- and the multifocus excitation schemes with the condition to obtain the same CARS signal in the same frame rate. For the evaluation of cell viability, we employed 4′,6-diamidino-2-phenylindole (DAPI) fluorophores that predominantly stained the damaged cells. One- and two-photon fluorescence of DAPI fluorophores were, respectively, excited by an ultraviolet light source and the same near-infrared light source and were monitored to evaluate the cell viability during near-infrared pulsed laser irradiation. We found lower uptake of DAPI fluorophores into HeLa cells during the multifocus excitation compared with the single-focus excitation scheme in both the one- and the two-photon fluorescence examinations. This indicates a reduction of photo-induced cell damage in the multifocus excitation. Our findings suggested that the multifocus excitation scheme is expected to be suitable for CARS microscopy in terms of minimal invasiveness.